The Impact of Type VI Secretion System, Bacteriocins and Antibiotics on Bacterial Competition of Pectobacterium carotovorum subsp. brasiliense and the Regulation of Carbapenem Biosynthesis by Iron and the Ferric-Uptake Regulator - Shyntum, Divine Yufetar; Nkomo, Ntombikayise Precious; Shingange, Ntwanano Luann; Gricia, Alessandro Rino; Bellieny-Rabelo, Daniel; Moleleki, Lucy Novungayo (Frontiers in Microbiology, 2019)
The complexity of plant microbial communities provides a rich model for investigating biochemical and regulatory strategies involved in interbacterial competition. Within these niches, the soft rot Enterobacteriaceae (SRE) comprise an emerging group of plant-pathogens causing soft rot/blackleg diseases resulting in economic losses worldwide in a variety of crops. In this report, a range of molecular and computational techniques were used to determine the contribution of antimicrobial factors such as bacteriocins, carbapenem and type VI secretion system (T6SS) in interbacterial competition among plant-pathogens/endophytes using an aggressive SRE as a case study (Pectobacterium carotovorum subsp. brasiliense strain PBR1692 – Pcb1692). A preliminary screening using next-generation sequencing of 16S rRNA comparatively analyzing healthy and diseased potato tubers, followed by in vitro competition assays, corroborated the aggressiveness of Pcb1692 against several taxa from Proteobacteria to Firmicutes. The results showed growth inhibition of several Proteobacteria by Pcb1692 depends either on carbapenem or pyocin production. Whereas for targeted Firmicutes, only pyocin seems to play a role in growth inhibition by Pcb1692. Although T6SS confers no relevant advantage during in vitro competition, a significant attenuation in competition by the mutant strain lacking a functional T6SS was observed in planta. Furthermore, production of carbapenem by Pcb1692 was observably dependent on the presence of environmental iron and oxygen. Additionally, upon deletion of fur, slyA and expI regulators, carbapenem production ceased, implying a complex regulatory mechanism involving these three genes. Furthermore, we unveiled the striking role played by S-pyocin in growth inhibition within the SRE group.